59 IMPROVING DELIRIUM AWARENESS AMONGST JUNIOR DOCTORS IN A REGIONAL HOSPITAL. (25th October 2022) - Condon, C; Connaughton, R; Keady, N; Martin, M
Abstract: Background: Delirium is a common medical emergency which is well known to be associated with adverse outcomes but often remains under recognised and inappropriately managed in the acute care setting. This audit aimed to assess Non-Consultant Hospital Doctors (NCHDs) approach to diagnosing, managing and prescribing in patients with delirium. Methods: Data was collected via an anonymous questionnaire and distributed to NCHDs in April 2021 and repeated again in March 2022 following several education sessions on delirium and the inclusion of the 4AT screening tool in the medical admission pro-forma. A point prevalence survey on 20 randomised patient charts was completed in April 2022 to establish if a 4AT score was documented by NCHDs in the medical admission pro-forma. Results: Two audits were completed over a one-year period between April 2021 and March 2022 including NCHDs, n=25 and n=26 respectively. The results showed that 56% vs 70% considered delirium as a medical emergency, 40% vs 77% stated that they used the 4AT tool when assessing cognition in patients aged over 65 years of age and 72% vs 76% stated that they did not use any guideline when prescribing a medication for a patient with delirium. However, on review of 20 medical charts, 0% of patients had a documented 4AT score completed on admission in April 2022. Conclusion: Although there was a positive improvement in NCHD's knowledge of delirium diagnosis and management on paper, it was evident that this did not transpire into clinical practice. We will address this by delivering further education sessions on delirium, with a plan to re-audit. We have also made the National Delirium Algorithms visible in the emergency department and on the wards to act as visual prompts for our NCHDs.